Understanding the research landscape of over-the-counter herbal products, dietary supplements, and medications evaluated for depressive symptoms in adults: a scoping review - Frost, Rachael; Zamri, Aiman; Mathew, Silvy; Salame, Adriana; Bhanu, Cini; Bhamra, Sukvinder K.; Bazo-Alvarez, Juan Carlos; Heinrich, Michael; Walters, Kate (Frontiers in Pharmacology, 2025)
BackgroundOver-the-counter (OTC) products such as herbal medical products (HMPs) or dietary supplements are a valued part of preventative and supportive self-care for depressive symptoms, but there is a wide array of products available, with differing levels of clinical evidence. It is unclear what the optimal directions for future research in this field are.AimWe aimed to explore the size and nature of the evidence base available for OTC products for depression in adults aged 18–60.MethodsWe carried out a scoping review following Joanna Briggs Institute guidance. We searched MEDLINE, Embase, PsycINFO, AMED, and CENTRAL from inception to December 2022, and 10% of the results were screened by two authors and the remainder by one author. We included randomised controlled trials of products commonly available OTC in multiple countries in participants with symptoms or a diagnosis of depression. Results were narratively summarised by the product and volume of evidence available.ResultsOut of 23,933 records found, we screened 1,367 full texts and included 209 trials. The largest volume of evidence was for omega-3s, St John’s Wort, saffron, probiotics, and vitamin D. Among a range of herbal medical products with promising evidence, those most commonly used and thus warranting further research were lavender, lemon balm, chamomile, and Echium. For 41 products, we found only single trials. Few products presented safety issues, whether used alone or adjunctively with antidepressants.ConclusionProducts with limited but promising evidence included folic acid, lavender, zinc, tryptophan, Rhodiola, and lemon balm, and future research should focus on these products. There is a need for further evaluation of herbal medical products as adjuncts to antidepressants and for exploring their potential benefits when used adjunctively with psychological therapies to support a more integrative approach. Safety reporting in these trials needs to be further improved.Systematic Review Registration:https://osf.io/rkm57/.